Maternal Dietary Glycemic and Insulinemic Indexes Are Not Associated with Birth Outcomes or Childhood Adiposity at 5 Years of Age in an Irish Cohort Study. Issue 6 (2nd May 2019) - Chen, Ling-Wei; Navarro, Pilar; Murrin, Celine M; Mehegan, John; Kelleher, Cecily C; Phillips, Catherine M
ABSTRACT: Background: High maternal dietary glycemic index (GI) and glycemic load (GL) may be associated with adverse offspring birth and postnatal adiposity outcomes through metabolic programming, but the evidence thus far, mainly from studies conducted in high-risk pregnant populations, has been inconclusive. No study has examined the influence of maternal insulin demand [measured by food insulinemic index (II) and insulinemic load (IL)] on offspring outcomes. Objectives: We investigated associations between maternal GI, GL, II, and IL and offspring birth outcomes and postnatal adiposity in a general pregnant population. Methods: The study was based on data from 842 mother-child pairs from the Lifeways prospective cohort study in Ireland. Through the use of standard methodology, maternal GI, GL, II, and IL were derived from dietary information obtained via a validated food-frequency questionnaire in early pregnancy (12–16 wk). Birth outcomes were abstracted from hospital records. At 5-y follow-up, children's body mass index (BMI) and waist circumference were measured. Associations were assessed through the use of multivariable-adjusted regression analysis. Results: Mothers had a mean ± SD age of 30.3 ± 5.7 y and a mean BMI (kg/m 2 ) of 23.9 ± 4.2. The mean ± SD for dietary glycemic and insulinemic indexes were: GI = 58.9 ± 4.4; GL = 152 ± 49; II = 57.4 ± 14.5; IL = 673 ± 267. After adjustment for confounders, no consistent associations were observed between maternal GI, GL, II, and IL and birth outcomes including birth weight, macrosomia, gestational age, and postterm births. Similarly, no association was observed with BMI and waist circumference z scores and childhood obesity (general and central) at 5-y follow-up. There was no evidence of a nonlinear relation between the studied indexes and outcomes. Conclusions: We observed no clear relation between maternal GI, GL, II, and IL and offspring birth outcomes and childhood obesity in a general pregnant population.